Dominant Dramatic and Resistance To Public Figure Communication Styles - Ubaydillah, Ahmad; Khaerudin Imawan (Indonesian Journal Publisher, 2026)
This study analyzes how national online media construct and respond to the dominant and dramatic communication style of public official Purbaya Yudhi Sadewa. The research aims to (1) examine how media framing constructs Purbaya’s communication style, (2) identify the representation of dominant and dramatic communication characteristics in quoted statements and media narratives, and (3) explain media resistance mechanisms that emerge through framing practices. Using a descriptive qualitative approach, this study applies Robert N. Entman’s Framing Theory and James McCroskey’s Communication Style Theory. The data consist of news articles published by four national online media outlets, CNN Indonesia, Tempo.co, Kompas.com, and Detik.com, during the period from September 8 to November 30, 2025. Data were collected through documentation of selected news texts and analyzed by examining framing elements and communication style indicators across media outlets. The findings show that each media outlet constructs Purbaya Yudhi Sadewa’s communication style differently according to its editorial orientation. CNN Indonesia and Tempo.co tend to normalize dominant and dramatic communication as part of institutional authority through technocratic and policy-oriented framing, resulting in minimal media resistance. In contrast, Kompas.com produces normative resistance by evaluating communication style based on public communication ethics, while Detik.com emphasizes dramatic and confrontational elements, generating symbolic resistance through sensational and conflict-oriented framing. The study concludes that media resistance toward a public official’s communication style is not uniform, but is shaped by selective framing strategies and editorial priorities, demonstrating the media’s active role in constructing public perception rather than merely reflecting individual communication traits.